2021
DOI: 10.2147/copd.s338560
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Reduction of Sedentary Time Following Tiotropium/Olodaterol Therapy in Treatment-Naïve Chronic Obstructive Pulmonary Disease

Abstract: Background: Prolonged sedentary behavior is associated with worse prognosis in patients with chronic obstructive pulmonary disease (COPD). Our previous study found that first-line dual therapy with tiotropium/olodaterol significantly reduces sedentary time compared to tiotropium monotherapy in Japanese patients with treatment-naïve COPD, although the characteristics of responders to dual-therapy versus monotherapy for COPD are still unclear. Methods: Patients with treatment-naïve COPD were randomized to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Other parameters, such as changes of forced expiratory volume in 1 s and the transient dyspnea index, were more improved by dual therapy than monotherapy. We also reported that COPD patients with lower inspiratory capacity or shorter time spent on activity of more than 2.0 METs before dual therapy had a significantly greater reduction in sedentary time after dual therapy [ 118 ]. These data showed that sedentary behavior time was reduced because of improvement of decreased inspiratory capacity, which contributes to shortness of breath and dyspnea, by dual bronchodilator therapy.…”
Section: Possible Interventions Focused On Physical Activity Especial...mentioning
confidence: 99%
“…Other parameters, such as changes of forced expiratory volume in 1 s and the transient dyspnea index, were more improved by dual therapy than monotherapy. We also reported that COPD patients with lower inspiratory capacity or shorter time spent on activity of more than 2.0 METs before dual therapy had a significantly greater reduction in sedentary time after dual therapy [ 118 ]. These data showed that sedentary behavior time was reduced because of improvement of decreased inspiratory capacity, which contributes to shortness of breath and dyspnea, by dual bronchodilator therapy.…”
Section: Possible Interventions Focused On Physical Activity Especial...mentioning
confidence: 99%
“…ST can be more strongly influenced by the wearing time than the duration of PA, simply because ST accounts for the majority of the measurement time. The minimum required wearing time was reported to be set to 8 [31], 10 [130,132-134], or 12 h [67,128,131,135] in previous studies, and the wearing time tended to be longer for SB assessments than for PA assessments. Further research is needed to confirm the optimal wearing time for evaluating ST.…”
Section: Minimum Required Wearing Time Per Daymentioning
confidence: 99%
“…Physical activity (PA) in patients with respiratory failure is a significant prognostic factor for mortality due to severe exacerbation [ 8 , 9 ]. In particular, PA in patients with severe respiratory failure tends to decrease due to disease management [ 10 ].…”
Section: Introductionmentioning
confidence: 99%